Analisis Produksi dan Pendapatan Petani Karet di Kabupaten Bungo - Jonni Ali; Arman Delis; Siti Hodijah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2015)
The purpose of this study was to identify the characteristics of rubber farmers, to determine and analyze revenue and  profit    rubber production in the sample, to determine and analyze the level of income    inequality  rubber  farmers  of  the  people  in the sample,  and to identify   and   analyze  the factors that affect smallholder rubber production in the sample. Based on these results suggested to the government should work closely with farmers in encouraging the opening of degraded land through various cooperation for optimal land use, because the land proved to have a significant influence on people's rubber production in Bungo.